Removal of Acid Fuchsin Dyem from Industrial Effluents Using Green Synthesized Copper Oxide Nanoparticles and their Characterization - Anbarasan, V.; Ibrahim, P.S. Syed; Jeyakumar, J. Edward (Journal of Applied Solution Chemistry and Modeling, 2025)
Nanoparticles are the spearheads of the rapidly expanding field of nanotechnology. Development of the green synthesis has gained extensive attention as a reliable, sustainable and eco-friendly protocol for synthesizing a wide range of metal and metal oxide nanoparticles. The synthesized copper oxide nanoparticles were characterized by ultraviolet visible spectroscopy (UV-Vis), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), Energy Dispersive X-ray (EDX). Adsorption parameters such as Initial dye concentration, Adsorbent dosage, pH, contact time, and temperature have also beenstudied. Adsorption isotherms namely Langmuir, Freundlich, Temkin are used to test the adsorption data; Kinetic studies such as pseudo first order, pseudo second order and thermodynamic parameters were also evaluated. To synthesis copper oxide nanoparticles, a green chemical strategy is employed in the current work. It is an easy, affordable, and effective alternative method. The green copper oxide nanoparticles that were made may be a good choice for removing dye from coloured aqueous solution due to their strong dye adsorption ability. CuO nanoparticle prepared from above mentioned routes is expected to have more extensive applications such as chemical sensor, catalytic, gas sensor, semiconductor etc. This method is the most viable in terms of energy, time, and simplicity. This procedure resulted in the production of copper Oxide nanoparticles on a huge scale.